Bologna, EMT and CIUTI – Approaches to High Quality in Translation and Interpretation Training - Schmitt, Peter (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
The quality of products and services, as well as methods of quality control are receiving more and more attention in industry, education, training and research. Translation and interpretation-related approaches towards better quality control include the generic ISO 9000 series (first published in 1987) as well as translation-specific standards such as the German DIN 2345 (1996), the American SAE J2450 (2001, 2005), and the European DIN EN 15038 (2006). CIUTI, an organization initiated in 1960, is the earliest approach to ensure high quality standards in translation and interpretation training and research. The European Higher Education Reform (Bologna Process), completed in 2010, was also a chance to improve the quality of university translation and interpretation programmes. Another and strictly outcome-oriented approach to improve translation quality is the relatively recent EMT project of the EU Commission. This paper describes how the different approaches of the Bologna Process, EMT, and CIUTI contribute to translation quality.